2020
DOI: 10.1186/s12935-020-01412-7
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA & Wnt signaling in colorectal cancer

Abstract: The outlook for new therapeutic approaches is pivotal to ameliorate the deterioration caused by the abrogated Wnt signaling. Long non-coding RNAs ( lncRNAs ) are tiny molecules that have begun emerging as vital molecular manager for the regulation of various cellular processes at transcription and translation levels in the colorectal cancer (CRC). Targeting Wnt pathway with lncRNA seems a promising approach to eradicate CRC. However, little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“… 9–11 lncRNAs are engaged in a wide array of diverse physiological and pathological processes through gene regulation at the transcriptional, post-transcriptional, or translational level. 12 , 13 Currently, lncRNAs have received considerable attention as novel critical controllers of cancer oncogenesis and progression. 14 Aberrant lncRNA expression has been widely reported in TSCC, and their dysregulation is implicated in the regulation of numerous cellular processes of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“… 9–11 lncRNAs are engaged in a wide array of diverse physiological and pathological processes through gene regulation at the transcriptional, post-transcriptional, or translational level. 12 , 13 Currently, lncRNAs have received considerable attention as novel critical controllers of cancer oncogenesis and progression. 14 Aberrant lncRNA expression has been widely reported in TSCC, and their dysregulation is implicated in the regulation of numerous cellular processes of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest EBLN3P as a novel biomarker for CRC cases. In recent years, growing studies have revealed that lncRNAs serve as regulators in CRC progression (22). For instance, lncRNA SNHG7, an overexpressed factor in CRC specimens, was found to promote the proliferation and metastasis of tumor cells via upregulating GALNT1 (23).…”
Section: Discussionmentioning
confidence: 99%
“…H19 is another related LNC in WNT signaling in metastasis of colorectal cancer. H19 has a role in metastasis, proliferation, and drug resistance in many types of cancers [54]. Increased expression of H19, also correlates with poor prognosis [55].…”
Section: Discussionmentioning
confidence: 99%